Carotid-Cavernous Fistula Manifesting as Symptomatic Bradycardia: A Unique Presentation. (August 2015) - Wadley, Sean M.; Patterson, Michael; Markowitz, Bethany; Patel, Rakesh; Graham, Cole Blease
ABSTRACT A 54-year-old female with vertigo and sarcoidosis presented to the emergency department with a 4-day history of generalised malaise, headache, fever, and near syncope. She was noted to have severe bradycardia and was admitted for possible pacemaker implantation. During the admission, the patient voiced left eye complaints, the workup of which revealed a left internal carotid aneurysm that ruptured, causing a direct carotid-cavernous fistula. The patient underwent multiple procedures to tamponade the fistula, and the bradycardia resolved, avoiding pacemaker implantation.